New foods changes and advances in technologies [videorecording] (Films Media Group, 2009)
Food product development is a continual process shaped by consumer demand, corporate objectives, and, perhaps most importantly-technological changes. This program shows how advances in technology are linked with the innovation of grocery and food-service products with the twin objectives of boosting health benefits and introducing items that have never been seen on the market. New techniques and approaches, such as microencapsulation, gene technology, an emphasis on novel and functional foods, and the development of packaging made from food products, highlight the changing landscape of the food industry.